The Effect of Journaling Techniques in Lowering Anxiety Levels in Grade XI Students in Facing Exams at SMA Colombo Leman DI Yogyakarta - Ahmad Rosul; Rahmanisa Murtaja Naswariski; Delara Lika Maulina (Green Publisher Indonesia, 2024)
Anxiety is a condition that is often experienced by every individual without exception, including being felt by students in order to prepare for the exam. In order to minimize anxiety conditions, the Journaling Technique is one of the Journaling Techniques for behavior modification intervention techniques in the formation of positive behaviors that can be done easily. The research was carried out at SMA Colombo Sleman, D.I.Yogyakarta involving 75 grade XI students who will take the grade promotion exam. The research method used was a quantitative pre-experimental design without a control group with the One-Group Pretest-Posttest Design research type. The results of the study showed a decrease of 14.25 in the average score of anxiety level of students of SMA Colombo Sleman, D.I Yogyakarta. So it can be said that there is an influence of journaling techniques in reducing students' anxiety levels when facing exams.